KAJIAN KARAKTERISTIK COOKIES SUBTITUSI TEPUNG SUKUN - Tobianus Hasan; Yohanes Don Bosko Demu; Asmulyati Saleh (Kupang Journal of Food and Nutrition Research, 2022)
Introduction: One of the nutritional problems that greatly contributes to malnutrition is protein energy deficiency (PEM). Malnutrition is a medical condition caused by inadequate or inadequate food intake or nutrition in terms of quantity, type, and quality of nutrition for a long period of time. Breadfruit contains various types of main nutrients, namely 25% carbohydrates, 1 protein, 5% and 0.3% fat by weight of breadfruit. In addition, breadfruit also contains calcium (Ca), phosphorus (P) and iron (Fe), vitamins B1, B2 and C.Methods: This type of research is experimental, using a completely randomized design (CRD) with three treatments (P). Treatment (P1) was substitution of 25% breadfruit flour and 75% wheat, treatment (P2) was substitution of 50% breadfruit flour and 50% wheat and treatment (P3) was substitution of 75% breadfruit flour and 25% wheat. The three types of cookies that were substituted for breadfruit flour were tested using the hedonic test. The most preferred product by the panelists will be analyzed for nutrient content. The data in this study were analyzed using the test (ANOVA).Results: The results of organoleptic tests (taste, aroma, texture and color) of cookies can be seen that on average the panelists prefer cookies with P1 treatment. Conclusions: 1. Breadfruit flour substitution has an effect on the organoleptic properties of cookies. 2. Substitution of breadfruit flour up to 50% is the best substitution that is organoleptically acceptable 3. The nutritional content of cookies with breadfruit flour substitution is 50% higher than the original cookies. 4. In every 100 grams of cookie ingredients contain 1.03% water nutritional value, 1.60% total ash or minerals, 2.88% fat, 7.87% protein and 0.3441 Kcal carbohydrates.